Impact of exclusion netting row covers on arthropod presence and crop damage to 'Honeycrisp' apple trees in North America: A five-year study. (August 2017) - Chouinard, G.; Veilleux, J.; Pelletier, F.; Larose, M.; Philion, V.; Cormier, D.
Abstract: Exclusion nets have been used successfully in France against codling moth Cydia pomonella (L.) since the early 2000s. Such a system has been adapted for North American conditions and was tested in an experimental apple orchard ('Honeycrisp') in southern Quebec, Canada from 2012 to 2016. Evaluation of insect and disease damage, as well as physical and physiological damage, was made in complete exclusion plots—in which the soil is also excluded—and in unnetted control plots. The exclusion system proved to be an effective protection device for the vast majority of key pests of apple fruit in most years. Damage from key insect pests such as the apple maggot Rhagoletis pomonella (Walsh), the tarnished plant bug Lygus lineolaris (Palisot de Beauvois) and the codling moth was significantly lower in netted plots than in unnetted plots. However, obliquebanded leafroller Choristoneura rosaceana (Harris) damage increased over the years to the point of being significantly more important in netted plots in 2015. Minimal or non-significant effects were observed on smaller, foliar pests, while highly significant protection effects were recorded for abiotic damage from frost and hail events that occurred during the study. Nets showed a significant protective effect on diseases such as apple scab Venturia inaequalis (Cooke) G. Wint., Gymnosporangium spp. rusts, and sooty blotch and flyspeck (SBFS) complex, when these were present in our plots. Highlights: Exclusion nets (mesh size: 1.90 mm × 0.95 mm) were effective in preventing or reducing damage from key apple fruit pests. Minimal effects were observed on foliar pests, and highly significant protection was recorded for damage from frost and hail. On some occasions nets had a significant protective effect on diseases such as scab, rust, and sooty blotch and flyspeck. The obliquebanded leafroller developed as well or better in netted trees than in unnetted trees.